PENINGKATAN KEMAMPUAN PEMASARAN DIGITAL PADA UMKM DI DESA SUMBANG PURWOKERTO UNTUK MENINGKATKAN DAYA SAING DAN JANGKAUAN PASAR - Maharani, Destin Alfianika; Hasibuan, Reza Rahmadi (Sekolah Tinggi Ilmu Ekonomi AMA, 2024)
This community service program was motivated by the problem of low utilization of digital marketing among MSMEs in Sumbang Village, Purwokerto, with 70% of participants not optimally using social media and only 30% utilizing the marketplace. The purpose of this program is to improve digital marketing skills through participatory training and intensive mentoring. The methods used include needs analysis, training sessions, and direct practice in the field. The evaluation results showed that 85% of participants started actively using social media, 60% succeeded in creating business accounts in the marketplace, and there was an increase in customer interaction of 75%. In addition, 45% of participants reported an increase in sales after utilizing paid advertising, and 90% of participants were able to use digital analysis tools such as Google Analytics to monitor the effectiveness of their campaigns. This program has succeeded in providing a positive impact on MSMEs in Sumbang Village, improving digital marketing skills that are essential to compete in a competitive market. It is recommended to continue the program with follow-up sessions and collaboration with third parties for ongoing support for MSMEs.